The Impact of Variables on Particle Size of Solid Lipid Nanoparticles and Nanostructured Lipid Carriers; A Comparative Literature Review - Leila Azhar Shekoufeh Bahari; Hamed Hamishehkar (Advanced Pharmaceutical Bulletin, 2016)
During the past decade, pharmaceutical science has seen rapid growth in interest for nanoscale materials. Solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) are popular research topics recently introduced as nano-scale drug carriers; they have shown numerous merits in drug delivery. Size is the most important index in a nanocarrier affecting its drug delivery efficiency. The influence of preparation conditions and type of lipidic components on the size of SLN and NLC in comparable states seems to be interesting for researchers who investigate these types of carriers. This review highlights the results of SLN and NLC particle size and size distribution comparisons.